Land and small farmer resistance in authoritarian Egypt. (23rd June 2022) - Bush, Ray
Abstract: This article examines small farmer resistance in Egypt. It situates contemporary struggles in the context of the uneven success of small farmers' historical resistance to land dispossession and neoliberal reform. Struggles over land are the prime driver of rural conflict and small farmers contest state strategies that reward local elites, land owners, and supporters of the military regime. There may not be a coherent social movement able to resist contemporary patterns of capital accumulation, but there are elements of resistance that edge forward an agenda for a "political conversation" about much‐needed deep social reforms. The internationally‐supported Sisi presidency has used violence to consolidate military power, making open revolt difficult. Nevertheless, small farmers link struggles over access to land with poor state provisioning of water and infrastructure as a means of building resistance.